Balancing the Scales: Achieving Equitable Teacher Distribution in Wajo Regency’s Elementary Schools - Wahyu Sriyani Kadir; Udik Budi Wibowo (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research is based on the problem of gaps in teacher distribution in Wajo Regency, there are schools that have an excessive number of teachers, but there are also schools that experience a shortage of teachers in several areas of Wajo Regency. The aim of this research is to analyze the condition of teacher equality in terms of recruitment, placement and distribution of teachers in Wajo Regency, the factors causing teacher inequality and the efforts made by the regional government to overcome this problem. This research uses a qualitative approach. Data collection methods are interviews, observation and document study. Data sources were obtained from the Head of the Wajo Regency Cultural Education Service, the Secretary of the Wajo Regency Education and Culture Service, the Chair of the Wajo Regency PGRI, school supervisors and school principals from Tempe District, Bola District and Gilireng District. The research results found that the condition of equal distribution of teachers in Wajo Regency still needs attention. It was found that several schools still lacked teachers and there were still many teachers who did not meet the specified qualifications. This is based on the geographical conditions and inadequate school infrastructure, especially schools in rural areas.  The Wajo Regency Government continues to make efforts optimizing the distribution of teachers so that there is no longer a gap in teachers within a school. This will certainly have a big influence on educational progress in Wajo Regency.